TEMPERATURE MAPS FOR FRICTIONAL HEATING IN DRY SLIDING - ASHBY, MF; ABULAWI, J; KONG, HS (SOC TRIBOLOGISTS & LUBRICATION ENGINEERS, 1991)
When contacting solids slide, work is done against friction. Almost all the frictional work appears as heat, generated at or very close to, the surface at which the two solids meet. The local increase in temperature influences both the friction and the rate of wear. In this paper, frictional heating is analyzed using a particularly simple framework. The analysis provides for a wide range of geometries for the two contacting solids, which may differ in their thermal and mechanical properties, and may not be in perfect contact with the heat-sinks to which they are attached. The results are presented as temperature maps which show the surface temperature of a sliding couple over a wide range of load and sliding velocity.
Keywords: SPEEDS; ICE